Poems of the Elder Edda - Dunn, Charles W.; Terry, Patricia, 1929- (Book collections on Project MUSE., 1990)
A revised edition of Terry's classic Poems of the Vikings, long out of print. This edition has a new preface, updated references, and expanded notes and glossary. The translation itself has been extensively revised.